International Legal Regulation and Management of Space Waste on Celestial Bodies - Milanov, Aleksandar (Journal of Ecohumanism, 2024)
The present article explores the international legal regulation of space waste on celestial bodies and the ecological challenges that space missions will pose in the near future. The lack of a shared vision of whether space waste production should be minimized on celestial bodies is causing uncertainty in the planning of future space missions. Leading private space companies are proposing the transfer of dangerous space waste produced from Earth into outer space. The excessive generation of space waste would increase the risks of activities such as space tourism, and space research and will threaten scientific fields such as radio astronomy. The political alliances that exclude a priori third parties will increase the risk of a generation of unnecessary orbital space debris and space waste on celestial bodies because of the development of several space missions in the same field. The sustainability of space missions on celestial bodies and the protection of the outer space environment should become a guiding principle for both national and international legal regulation of space activities. This article argues for the urgent need to establish comprehensive international regulations and monitoring mechanisms to manage space waste on celestial bodies, emphasizing sustainability and cooperation among space-faring nations.